Faktor Preferensi Individu Muzakki Lembaga Zakat Informal - Sheila Ardilla Yughi (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
Taxes are one of the sources of state opinion that has been formally used to sustain This study aims to identify the dominant individual factors in terms of Muzakki's preference in choosing to pay zakat at the Informal Zakat Institution and provide recommendations related to efforts to increase the collection of zakat funds from the community. The research method used is descriptive analysis, factor analysis and mean analysis. Descriptive analysis was used to explain the demographics of respondents while factor analysis and mean analysis were used to obtain dominant individual factors affecting muzakki in paying zakat to the Informal Zakat Institution. The results of the study get the dominant individual factors that influence the payment of zakat to informal zakat institutions by calculating the composite value, respectively are faith, individual and social awareness (4.60), zakat knowledge (4.16), self satisfaction (3.71) , religiosity (3.60) and rewards and compensation (2.18). Suggestions given are Informal Zakat Institutions can be used as official OPZ partners from the existing Formal Zakat Institutions and the partnership is well socialized to the public and the Government needs to socialize that the zakat payments made can be used as a deduction of tax payments.